2007
DOI: 10.3952/lithjphys.47418
|View full text |Cite
|
Sign up to set email alerts
|

Amplified luminescence and generation dynamics of the diode pumped erbium-ytterbium laser

Abstract: The influence of the cavity trapped amplified luminescence (CTAL) on the threshold, power and dynamic characteristics of Er, Yb : glass lasers with end and side diode pump configurations has been studied. The CTAL loss coefficient has been evaluated using the luminescence balance equation. The inverse proportion dependence of the CTAL loss coefficient on the cavity length has been revealed. It has been shown that amplification of luminescence in the laser cavity leads to a significant increase of the threshold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…At that, the behaviour of the curves 1 and 2 remains the same. These results are in agreement with [12] where it has been shown that amplified spontaneous emission can both increase and decrease the laser turn-on time depending on the pumping and cavity characteristics. The dependences of the pulse delay on the active element length at different ξ factors and fixed cavity length L = 100 mm are shown in Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…At that, the behaviour of the curves 1 and 2 remains the same. These results are in agreement with [12] where it has been shown that amplified spontaneous emission can both increase and decrease the laser turn-on time depending on the pumping and cavity characteristics. The dependences of the pulse delay on the active element length at different ξ factors and fixed cavity length L = 100 mm are shown in Fig.…”
Section: Resultssupporting
confidence: 92%
“…Active medium ytterbium and erbium doping concentrations were selected to be 4·10 27 and 5·10 25 m −3 , respectively. Yb, Er:glass and Co:MgAl 2 O 4 passive Q-switch parameters were taken from [12] and [16] respectively. Two-side transverse pumping of the cylindrical glass active element was assumed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations